2009
DOI: 10.1016/j.jhep.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of hepatocellular carcinoma among liver-related causes of deaths in HIV-infected patients: The French national Mortalité 2005 study

Abstract: word count: 197Text word count: 3334 (abstract excluded)Figures: 2 Tables: 3 ABSTRACT: Background. Longer exposure to hepatitis C (HCV) or B virus (HBV) and the increased use of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 35 publications
3
62
2
1
Order By: Relevance
“…HCC has become a major problem in HIV/HCVcoinfected patients [29], as highlighted in the previous Mortalité 2005 study [30]. In this study, 12 patients died from HCC and the majority of cases (nine out of 12) were related to HCV infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…HCC has become a major problem in HIV/HCVcoinfected patients [29], as highlighted in the previous Mortalité 2005 study [30]. In this study, 12 patients died from HCC and the majority of cases (nine out of 12) were related to HCV infection.…”
Section: Discussionmentioning
confidence: 66%
“…In 2010, improved access to HCV care and the increased rate of sustained virological response may have counterbalanced such detrimental factors and accounted for the stabilization of liver-related mortality. Premature death of patients with severe chronic liver diseases during the first decade (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) may have positively impacted LRD mortality in 2010.HCC has become a major problem in HIV/HCVcoinfected patients [29], as highlighted in the previous Mortalité 2005 study [30]. In this study, 12 patients died from HCC and the majority of cases (nine out of 12) were related to HCV infection.…”
mentioning
confidence: 99%
“…41 The use of nucleoside analogues, particularly with zidovudine and stavudine, is associated with hepatic steatosis. 42 HIV-positive patients presenting with HCC appear to be younger (52 versus 64 years, P < 0.001), to be more frequently symptomatic at presentation, to have multiple tumors or invasive disease, and to have advanced tumors in comparison with HIV-negative patients. 20,43 No data are available about the costeffectiveness of screening for HCC in HIV-positive patients with cirrhosis.…”
Section: Nonviral Etiologiesmentioning
confidence: 94%
“…Studies have shown that excessive consumption of alcohol appears to be a cofactor that increases mortality from liver disease in co-infected patients [40,47]. Most cases of liver associated mortality in co-infected patients are due to end-stage liver disease or hepato-cellular carcinomia [48].…”
Section: Route Of Transmissionmentioning
confidence: 99%